2016
DOI: 10.1371/journal.pone.0165879
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Hepatitis B Vaccination Strategies to Prevent Perinatal Transmission in North Korea: Selective Vaccination vs. Universal Vaccination

Abstract: BackgroundTo tackle the high prevalence of Hepatitis B virus (HBV) infection in North Korea, it is essential that birth doses of HBV vaccines should be administered within 24 hours of birth. As the country fails to provide a Timely Birth Dose (TBD) of HBV vaccine, the efforts of reducing the high prevalence of HBV have been significantly hampered.MethodsTo examine the cost-effectiveness of vaccination strategies to prevent perinatal transmission of HBV in North Korea, we established a decision tree with a Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Lee and Park used a Markov model to establish cost effectiveness of different vaccination strategies for the prevention of perinatal HBV transmission in the DPRK and showed that selective vaccination may be more cost-effective than universal vaccination 15…”
Section: Resultsmentioning
confidence: 99%
“…Lee and Park used a Markov model to establish cost effectiveness of different vaccination strategies for the prevention of perinatal HBV transmission in the DPRK and showed that selective vaccination may be more cost-effective than universal vaccination 15…”
Section: Resultsmentioning
confidence: 99%
“…Community health workers have been used effectively in HIV programmes, 54 distribution of malaria diagnostics and treatment 55 and contraceptives. Other nations have implemented selective vaccination as opposed to universal vaccination and found this to be highly cost effective 56 . This needs to be explored and considered as an alternative in Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%
“…The universal vaccination program was considered to be cost-utility when ICUR ≤ 3 times of the annual per capita GDP (CNY 115,000.00, US$ 17,683.60 in Beijing in 2016) and it was highly cost utility when ICUR does not exceed per capita GDP according to WHO recommendation. 49,50 We further estimated the QALY loss and direct treatment cost of each HB-related disease in different scenarios, to evaluate the health and economic burden due to HBV infection during cohort's lifetime.…”
Section: Cost-utility Analysismentioning
confidence: 99%